MODEL DAN STRATEGI PENGEMBANGAN BERBASIS KOMODITI UNGGULAN MASYARAKAT ENTIKONG KALIMANTAN BARAT PERBATASAN INDONESIA-MALAYSIA - Kardius Richi Yosada (STKIP Persada Khatulistiwa Sintang, 2021)
The vast area of border between Indonesia and Malaysia in West Kalimantan would require the support of border management systems are organized and professional, both at the central and regional levels. However, the lack of infrastructure in the border area has shown that the government does not have a good border management system. During this time, the responsibility for the management of border areas is merely coordinative between ministerial and non-ministerial government agencies, without a government agency directly responsible for border management from the central to regional levels. The approach used in this research is qualitative phenomenology with Existing Models. The form of Phenomeology Research used in this study has 4 steps, namely analyzing the phenomena that occur, determining the context, collecting data and field notes. The results of this study are the formation of the development and development of smallholder plantations in the form of Model for developing smallholder plantations in Entikong District can be divided into four types based on commodities, namely: 1) Pure Plantation Areas, Mixed Plantation Areas , Multipurpose Plantation Areas, Integrated Plantation Areas